Soroprevalência e fatores de risco para infecção por Toxoplasma gondii em ovinos no estado de Goiás - Moura, Catarina Elízia Bernardino Rates de (2021)
Toxoplasmosis is a zoonosis of wide distribution worldwide, caused by the protozoan Toxoplasma gondii, which can cause economic losses in sheep production mainly due to the appearance of reproductive disorders. In addition, sheep infected with T. gondii may represent a potential risk to human health, due to the large cystogenic capacity that some isolates of the parasite present, leading to the possibility of human infection through the ingestion meat from infected animals. In this sense, the objective of the aforementioned work was to evaluate seroprevalence and risk factors for Toxoplasma gondii infection in sheep in the state of Goiás, located Center-Western region of Brasil. For this purpose, through the indirect immunofluorescence reaction (IFA), 1000 serological samples from sheep from the 18 microregions were analyzed. of State. The data were analyzed using Pearson's chi-square test, which evaluated the possible risk factors for T. gondii (p≤0.05), with the odds ratio (OR) estimates obtained, with a confidence interval of (CI) 95%. The risk factors were calculated considering the risk for each animal, (calculated from the risk), using the software Statistica 10 (StartSot Inc., 2011). In 34.3% (343/1000) of the analyzed samples, the occurrence of anti- T. gondii antibodies (IgG) was observed with serological titers ≥ 64 to ≥ 65536 that varied in the regions from 18.1% (15/83) to 64.15% (34/53). In all regional unitis sampled in the state of Goiás, seroreagent animals were detected, being the age, the water, the form of replacement of the herd and the presence of domestic cats and wild animals, considering the risk factors statistically associated with the serum-occurrence of antibodies against Toxoplasma gondii in sheep.